Human gait symmetry and coordination assessment during treadmill walking using wearable ultrasonic sensors network - Lin, Eileen (2019)
The aim of this report is to investigate the effectiveness of the Wearable Ultrasonic Sensors Network in the gait analysis, which can be useful in rehabilitation process in the clinical setting. This report will talk about the findings and comparison between the high speed optical motion capture analysis system (current gold standard) and ultrasonic sensor (proposed system) to analyse the gait of the subject on the treadmill under different speed. For the Wearable Ultrasonic Sensors Network, Arduino will be used as the micro-controllers. For the Optical Motion Capture System Network, the Eagle camera and Cotex software will be used. The two set of data will be compared in the MATLAB for different temporal parameters of the gait such as the stance and swing time.